2009
DOI: 10.1039/b806437g
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic mass transport effects in electrocatalytic processes

Abstract: The role of mesoscopic mass transport and re-adsorption effects in electrocatalytic reactions was investigated using the oxygen reduction reaction (ORR) as an example. The electrochemical measurements were performed on structurally well-defined nanostructured model electrodes under controlled transport conditions in a thin-layer flow cell. The electrodes consist of arrays of Pt ultra-microelectrodes (nanodisks) of defined size (diameter approximately 100 nm) separated on a planar glassy carbon (GC) substrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
169
1
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(202 citation statements)
references
References 85 publications
22
169
1
10
Order By: Relevance
“…First, we show that simultaneous measurement of the H 2 O 2 current is vital for correct interpretation of ORR data. Second, while others have previously shown that the ORR catalyzed by large Pt nanoparticles is affected by changes in k t (22,23) we show here that this does not apply for smaller Pt materials. Finally, we show that the size of very small Pt nanoparticles (diameters <2 nm) has an effect on the mechanism of the ORR, and hence its product distribution.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…First, we show that simultaneous measurement of the H 2 O 2 current is vital for correct interpretation of ORR data. Second, while others have previously shown that the ORR catalyzed by large Pt nanoparticles is affected by changes in k t (22,23) we show here that this does not apply for smaller Pt materials. Finally, we show that the size of very small Pt nanoparticles (diameters <2 nm) has an effect on the mechanism of the ORR, and hence its product distribution.…”
mentioning
confidence: 56%
“…In most of these studies, k t is increased by decreasing the surface coverage of the catalyst (21-23, 27, 28). For example, Behm and coworkers studied the ORR using twodimensional arrays of 100-nm Pt islands immobilized on glassy carbon (GC) electrodes (22,23). The key finding was that the amount of electrogenerated H 2 O 2 increased with decreasing catalyst coverage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This experimental fact on extended catalytic surfaces, deduced via the RRDE technique, apparently supports the "direct pathway". However, recent studies [55][56][57] using the effect of mass transport put in evidence that an important amount of H 2 O 2 , on mesoscopic particle size of platinum, are generated. Interestingly, both studies used different approaches, namely, the single particle [55] and particle arrays.…”
Section: à2mentioning
confidence: 98%
“…Interestingly, both studies used different approaches, namely, the single particle [55] and particle arrays. [56,57] These latter are produced by colloidal lithography. Whereas the first approach obtained a maximum production of 25 % H 2 O 2 under high mass transport conditions, the second one (by varying the Pt coverage from 4 to 40 % on a glassy carbon substrate) produced a 10 to 20-fold increase in the H 2 O 2 yield.…”
Section: à2mentioning
confidence: 99%